Accessing the Anti-Proliferating Activity of Tankyrase-2 Inhibitors via 2D, 3D-QSAR and Molecular Docking: Assessment of Structure Activity Relationships - Mervat H. El-Hamamsy (Journal of Applied Pharmaceutical Science, 2017)
Tankyrases (TNKSs) have been implicated in many biological processes and have been proposed as a drug target for cancer therapy. The human genome encodes two homologous isoforms, TNKS-1 and TNKS-2. This study reported the first theoretical study of three-dimensional, two-dimensional quantitative structure activity relationships and a docking analysis of a series of 2-arylquinazolin-4-one, 3-arylisoquinolin-1-one, arylnaphthyridinone and aryltetrahydronaphthyridinone derivatives with remarkable TNKS-2 inhibiting activities reported recently in literatures. The predictive ability of the QSAR models was assessed using internal and external validation. 3D-QSAR model showed that the substituents R1 and R2 in studied compounds are key modulators to enhance the TNKS-2 inhibition. The 2D-QSAR model, was based mainly on three 2D descriptors and nine 3D descriptors. This suggested that TNKS-2 inhibition is predominantly controlled by steric properties of the inhibitors. Docking study was carried out by using ligands docking on the active site of three different crystal structures of TNKS-2 to understand the binding mode of these compounds as TNKS-2 inhibitors. We discussed the structural requirements for selective and potent TNKS-2 inhibitors. Four potent inhibitors were designed to be synthesized in the future.
Keywords: Tankyrase,QSAR,Docking,2-arylquinazolin-4-one,3-arylisoquinolin-1-one,arylnaphthyridinone.